Combined convection heat transfer of nanofluids flow over forward facing step in a channel having a blockage - Mohammed, H. A. (2013)
Numerical simulations of two dimensional laminar combined convection flows using nanofluids over forward facing step with a blockage are analyzed. The continuity, momentum and energy equations are solved using finite volume method (FVM) and the SIMPLE algorithm scheme is applied to examine the effect of the blockage on the heat transfer characteristics. In this project, several parameters such as different types of nanofluids (Al2O3, SiO2, CuO and ZnO), different volume fraction in the range of 1% - 4%, different nanoparticles diameter in the range of 25nm-80nm were used. Effects of different shapes of blockage (Circular, Square and Triangular) were studied. The numerical results indicated that SiO2nanofluid has the highest Nusselt number. The Nusselt number increased as the volume fraction and Reynolds number increase, while it decreases as the nanoparticles diameter increases. Circular blockage produced higher results compared to triangular and square one.